Analysis of the influence of environmental factors on the delay in the construction of Maluku traffic office service building - Sohilait, Matheos; Maelissa, Nelda; Nur Rokhim, Imam; Ahmad Bhat, Sartaj (Universitas Nahdlatul Ulama Surabaya, 2022)
The objective of this study was to analyze the factor of COVID-19 and environmental factors that affect the delay of building construction. The construction of the BPKB Service Building for the Traffic Directorate of the Maluku Regional Police in T.A 2020 was a project that spends a very large budget with a planned time of 150 days. Building construction was delayed up to 4 weeks. This building construction experienced a delay of 27.895% of the work that had to be done. The method used is principal component analysis, which is multivariate and transforms correlated original variables into new uncorrelated variables by reducing the number of these variables so that they have smaller dimensions but can explain most of the diversity of the original variables. The results of the analysis of 25 respondents and 3 variables, namely: building tents to anticipate rain, good and harmonious relationships to prevent unexpected things from happening, and checking the location before making soft drawings.